Genomic Reconstruction of the History of Native Sheep Reveals the Peopling Patterns of Nomads and the Expansion of Early Pastoralism in East Asia. (22nd June 2017) - Zhao, Yong-Xin; Yang, Ji; Lv, Feng-Hua; Hu, Xiao-Ju; Xie, Xing-Long; Zhang, Min; Li, Wen-Rong; Liu, Ming-Jun; Wang, Yu-Tao; Li, Jin-Quan; Liu, Yong-Gang; Ren, Yan-Ling; et al.
Abstract: China has a rich resource of native sheep ( Ovis aries ) breeds associated with historical movements of several nomadic societies. However, the history of sheep and the associated nomadic societies in ancient China remains poorly understood. Here, we studied the genomic diversity of Chinese sheep using genome-wide SNPs, mitochondrial and Y-chromosomal variations in > 1, 000 modern samples. Population genomic analyses combined with archeological records and historical ethnic demographics data revealed genetic signatures of the origins, secondary expansions and admixtures, of Chinese sheep thereby revealing the peopling patterns of nomads and the expansion of early pastoralism in East Asia. Originating from the Mongolian Plateau ∼5, 000‒5, 700 years ago, Chinese sheep were inferred to spread in the upper and middle reaches of the Yellow River ∼3, 000‒5, 000 years ago following the expansions of the Di-Qiang people. Afterwards, sheep were then inferred to reach the Qinghai-Tibetan and Yunnan-Kweichow plateaus ∼2, 000‒2, 600 years ago by following the north-to-southwest routes of the Di-Qiang migration. We also unveiled two subsequent waves of migrations of fat-tailed sheep into northern China, which were largely commensurate with the migrations of ancestors of Hui Muslims eastward and Mongols southward during the 12th‒13th centuries. Furthermore, we revealed signs of argali introgression into domestic sheep, extensive historical mixtures among domestic populations and strong artificial selection for tail type and other traits, reflecting various breeding strategies by nomadic societies in ancient China.